Avaliação cinemática, eletromiográfica e da concentração de biomarcadores inflamatórios em sujeitos com dor lombar : comparação de instrumentos de medida, avaliação de fatores que influenciam nos registros - Batistão, Mariana Vieira (2017)
Low back pain has negative impact on quality of life and work performance, and presents socioeconomic burden. Several studies have focused on investigating the dose-response relationship between risk factors and the development of low back pain. One way to evaluate this relationship is Surface Electromyography (EMG). Study 1 aimed to evaluate the influence of skinfolds, body mass index (BMI) and body mass on the amplitude of the EMG of the erector spinae (iliocostalis), multifidus and rectus abdominis muscles. Nineteen male subjects were recruited. The analysis showed that these factors influence the EMG record, explaining from 27 to 73% of the signal variance. Likewise, the evaluation of trunk movements and posture are of interest in ergonomic research. Study 2 aimed to compare two trunk movement logging systems, the three-dimensional movement recording system (Qualisys, ProReflex MCU, Sweden) and the inclinometer (Logger Tecknologi HB, Akarp, Sweden). Data from 27 volunteers were analyzed. Data were collected during three different tasks: a static in the orthostatic position, a static with 45 ° of trunk flexion and a dynamic being a manual handling of a load of 11.4 kg. The trunk movements were evaluated by the two systems simultaneously. The results showed that the systems differed between 0.9 ° in the standing static task, 10º in the static with trunk flexion and 29.3° in the dynamic task. Therefore, the use of inclinometer for posture evaluation and trunk movements should be done with caution, especially in the evaluation of dynamic tasks. In addition to the kinematic and electromyographic evaluation, another approach has been used. Recent studies have investigated the inflammatory response and its relationship to low back pain. Thus, the aim of Study 3 was to compare the levels of inflammatory biomarkers (TNF-α, IL-1β, IL-6 and IL-10) in workers with low back pain, according to the characteristics of the symptoms, such as: functional impact, search for professional help, symptoms in the last 7 days and frequency of symptoms in the last year. Twenty-four men were evaluated. The Elisa method (Enzyme-Linked Immuno Sorbent Assay - Quantikine®HS, R & D Systems, Minneapolis, USA) was used to quantify the level of cytokines. However, no statistical difference was found. And in Study 4, the objective was to quantify, at two different times, levels of inflammatory biomarkers in experienced workers with low back pain, randomly divided into two groups: control (did not perform a load handling task) and experimental (handled ). The ELISA method was used to quantify the concentration of cytokines in twenty-five male workers (control=13; experimental= 12). The results showed that no differences were found in the concentration of biomarkers between the groups nor between the evaluations. In this way, it can be concluded that the task did not modify the concentration of biomarkers. Recommendations for future studies are to evaluate a task that generates greater overload, that is, with a longer duration, frequency or magnitude, considering the risks imposed to the population.